RECYCLING OF AUTOMOBILE TIRES AND CONCRETE SCRAP IN THE INTERESTS OF ECO-ORIENTED INNOVATION DEVELOPMENT - E. Zimin (Вестник университета)
In article the question of processing of such types of waste as worn-out car tires and a concrete crowbar acquiring special relevance in the sphere of the ekologo-focused innovative development is considered. In article the main engineering procedures of a recycling of car tires both from the point of view of ecological safety, and from the point of view of achievement of the maximum economic effect are analysed. On the basis of the comparative analysis of values of the economic indicators received as a result of calculations the conclusion is drawn on considerable economic advantage of process of a termoliz which represents processing of tires by influence of organic solvent. The high profit, receiving high-quality materials when processing car tires, and also lack of negative influence on an ecological situation do this method the most acceptable and perspective.